The Innovation of Islamic Education Learning Through Quantum Learning Model - Zulkarnain; M. Yunus Abu Bakar; Nur Kholis; Siti Marfuah (TADRIS: Jurnal Pendidikan Islam, 2023)
The quantum learning model is a lively learning transformation with all its nuances that include all the links, interactions, and differences that maximise learning moments and focus on dynamic relationships in the classroom environment interactions that establish a foundation in order to learn. This study aims to elaborate on the implementation of the principles and steps of the quantum learning approach in PAI learning. The method used in the research is a Systematic Literature Review that starts from the process of searching for literature, screening and eligibility testing. The articles reviewed from 2017-2023 publications. The results showed that the implementation of quantum learning in PAI learning can be in the form of; (1) the application of quantum learning principles (everything speaks, everything aims, experience before naming, recognise every effort, if it is worth learning, then it is also worth celebrating, (2) the application of TANDUR steps, namely; Grow, Experience, Name, Demonstrate, Repeat, and Celebrate. Islamic Education Learning Innovation with Quantum Learning Model offers a new and promising approach to improve the quality of Islamic Education learning through active interaction and student empowerment. This research has the potential for personal empowerment.